ESTABLISHMENT OF PSYCHOLOGICAL SERVICE IN EDUCATION - Ibragimova Shaxnoza Gapparovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Focusing on the historical foundations of the organization of psychological services in education, the factors influencing and contributing to the successful implementation of the process of psychological services, which help to make decisions in accordance with the requirements of today’s socio-economic development